Analisis Pengaruh Serbuk Besi Sebagai Substitusi Agregat Halus pada Lataston Lapis Aus (HRS-WC) Terhadap Kinerja Jalan Beraspal - Nasrulloh, Moch; Sholichin, Ibnu; Fatikasari, Aulia Dewi (Jurnal Talenta Sipil, 2024)
Damage to flexible pavements is still commonly found in Indonesia. As technology develops, there is some research regarding using iron powder as an alternative replacement material for asphalt mixtures. This research used iron powder waste as a substitute for fine aggregate in Hot Rolled Sheet–Wearing Course with levels of 0%,15%,30%, and 45%. The purpose of this research to determine the Optimum Asphalt Content (OAC) and optimum percentage of iron powder waste addition as a substitute for fine aggregate to the indicator of Marshall test based on The General Specification of Bina Marga 2018 (Revision 2). Based on Marshall testing that has been carried out, the OAC values are 7,5% with an average of stability 2040,46 kg, flow 3,40 mm, MQ 600,24 kg/mm, voids in mix 4,69%, voids in mineral aggregate 18,30%, and voids filled with asphalt 74,39%. While the optimum percentage of iron powder value is 13% with an average of stability 2091,90 kg, flow 3,17 mm, MQ 662,79 kg/mm, voids in mix 3,92%, voids in mineral aggregate 17,59%, and voids filled with asphalt 77,72%. The result met the General Specification of Bina Marga 2018 (Revision 2). The addition of iron powder as a substitute for fine aggregate in HRS-WC is can increase stability but reduce air voids in the asphalt mixture.  This result makes the asphalt mixture more impermeable and plastic.